Smartphone Dynamic Infrared Thermography for Harvesting AICAP Flap in a Large Breast-conservative Surgery - Stefano Vaccari, MD; Valerio Lorenzano, MD; Andrea Lisa, MD; Riccardo Di Giuli, MD; Marco Klinger, MD; Francesco Klinger, MD; Valeriano Vinci, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Flaps based on perforators of the intercostal arteries have been described for the reconstruction of defects resulting from partial mastectomies. Dynamic infrared thermography (DIRT) identifies hot spots that accurately correspond to and evaluate perforator vessels toward the skin. The new generation of portable thermal cameras has become smaller, less expensive, more sensitive, and compatible with common smartphones. One option is the FLIR ONE system (FLIR Systems, Inc., Wilsonville, OR), a smartphone-compatible thermal camera. Despite its lower resolution, compared with the larger infrared camera models, it represents a viable option for thermal skin mapping, and its compact nature allows for easy portable use. The purpose of this article is to report a case of a preoperative study with smartphone DIRT used in the preparation of an anterior intercostal artery perforator–based flap for breast reconstruction after a wide resection at the level of the right infer-internal breast region, including a skin excision. Our study documents how smartphone DIRT is a rapid, sensitive, easily accessible and cost-effective diagnostic method for the topographical identification of intercostal artery perforators. It can be used as a rescue method at any stage of the intervention if it differs from the preoperative planning. It also confirms the proven usefulness of this flap for the reconstruction of partial defects in the breast and thoracic region.